Chronic Kidney Disease and Nutrition Support. (18th March 2021) - Chan, Winnie
Abstract: Individuals with chronic kidney disease (CKD), particularly those undergoing maintenance dialysis, are prone to protein‐energy wasting (PEW), the latter of which can be ameliorated with different methods of nutrition support. Dietary counseling guided by dietitians is the key for preventing and managing PEW in CKD. If dietary counseling per se fails to meet the recommended energy and protein requirements, the addition of oral nutrition supplements (ONSs) would be necessary. When these initial measures cannot attain the recommended energy and protein requirements, nutrition support, including enteral tube feeding or parenteral nutrition (PN), should be considered as a viable option to improve nutrition status. Partial PN, comprising intraperitoneal PN (IPPN) and intradialytic PN (IDPN) therapies, may be attempted as supplemental nutrition support in patients with PEW requiring peritoneal dialysis and hemodialysis, respectively. Despite the debatable effectiveness of IPPN for patients undergoing peritoneal dialysis, it remains a feasible means in these patients. The indications for IPPN in patients undergoing peritoneal dialysis include inadequate dietary intake of energy and protein, and barriers of oral intake and other forms of enteral supplementation such as issues with suitability, tolerance, and compliance. Nonetheless, in the case of spontaneous dietary consumption of energy and protein meeting the difference between the IDPN provision and the nutrition targets, the use of IDPN is rational. In patients with PEW and malfunctioning gastrointestinal tract, as well as those whose enteral intake (with or without partial PN) is below the recommended nutrient requirements, total PN becomes a relevant nutrition intervention.